Factors associated with joint mobility in an adolescent population. Issue 3 (March 1987) - Silman, A J; Day, S J; Haskard, D O
Abstract : Fixed torque devices were used to measure joint mobility at three sites in 364 adolescents including 39 families with at least two siblings. Increasing age and being male were associated with reduced laxity, and a strong effect of family was observed in the 39 sibling sets studies. The population included 47 Asians whose mobility was similar to that of the non-Asians, though the female/male difference was apparently greater in the former group. None of the above conclusions apply to index finger hyperextension, and it is apparent that genetic and constitutional factors only affect mobility at some sites. Such observations could lead to a review of current scoring systems for clinical hypermobility.